Gift of professional income generated by a spouse to a third person in Mauritian Civil Law - Georgijević Goran (Anali Pravnog Fakulteta u Beogradu, 2020)
For historical reasons, Mauritian civil law has been influenced by French civil law. However, despite the differences between Mauritian civil law and French civil law and the indisputable autonomy of the Mauritian civil law, it is impossible to deny that the latter is strongly inspired by the French civil law and that the Mauritian judge will in most cases refer to the decisions rendered by French courts - and in particular by the Court of Cassation - as well as to the French doctrine. This statement is applicable to Mauritian Law on Matrimonial Property Regimes which is inspired by French civil law. In this article we will first provide a brief overview of the Mauritian Law on Matrimonial Property Regimes, followed by an analysis of the validity of a gift of professional income generated by a married person to his concubine.